الاقتصاد الدائري كمدخل إبداعي للحد من البصمة البیئیة وتحقیق التنمیة السیاحیة المستدامة: دراسة نظریة وتحلیلیة - الرمیدي, بسام سمیر (Finance and Business Economies Review, 2018)
The study aimed to analyze the role of the circular economy in reducing the ecological footprint, the negative effects of tourism on the environment and achieving sustainable tourism development. The researcher relied on the descriptive and analysis approach to achieve the objective of the study. The study concluded that the circular economy represents the creative and strategic approach to reduce environmental degradation resulting from the negative practices of tourism activities, reduce the ecologicalfootprint and ensure the sustainability of tourism development.